La Vulva - Arauz, Carlos (Revista Universidad de Guayaquil, 1998)
The most extraordinary installationsuggestive intelligence toward mysterymonologue of happinessuniversal private dreamtunnel in infinite timewith the exalted functional blissincredible matrix with explosive chargedecálogo and synthesis of wondermotive of naïve and pure pressurecheckmate to the chessboard of loveall efforts lead to the centerof all things beautifully shapedthat women refinein accordance with horizontal conductknowledge and willingnessin the exercise of human goodsin transit through eternityframe of astonishing simplicityas life and death are evidence.